2019
DOI: 10.1101/825760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A peptide inhibitor of Tau-SH3 interactions ameliorates amyloid-β toxicity

Abstract: The microtubule-associated protein Tau is strongly implicated in Alzheimer's disease (AD) and aggregates into neurofibrillary tangles in AD. Genetic reduction of Tau is protective in several animal models of AD and cell culture models of amyloid-β (Aβ) toxicity, making it an exciting therapeutic target for treating AD. A variety of evidence indicates that Tau's interactions with Fyn kinase and other SH3 domain-containing proteins, which bind to PxxP motifs in Tau's proline-rich domain, may contribute to AD def… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…However, given the importance of Fyn in normal physiological processes, such therapy would be difficult, especially since dementia patients usually have reduced cognitive reserves. Thus, more specific therapies aimed at targeting either disease related processes involving Fyn or Fyn interaction partners may yield a more desirable therapeutic result; the recent report of a peptide inhibitor of the tau-Fyn interaction [ 65 ] is a first step in this direction. In closing, as Aβ oligomers had no role in these findings, Fyn alone has an important role in tauopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the importance of Fyn in normal physiological processes, such therapy would be difficult, especially since dementia patients usually have reduced cognitive reserves. Thus, more specific therapies aimed at targeting either disease related processes involving Fyn or Fyn interaction partners may yield a more desirable therapeutic result; the recent report of a peptide inhibitor of the tau-Fyn interaction [ 65 ] is a first step in this direction. In closing, as Aβ oligomers had no role in these findings, Fyn alone has an important role in tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pY18-tau also co-localized with activated Src family tyrosine kinases (SFK) in NFTs of FTDP-17 mouse brains [ 2 ]. In Aβ-mediated neurodegeneration, the importance of the tau-Fyn interaction has been supported by the finding that inhibition of the interaction ameliorated the toxic effects of Aβ oligomers [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…We then tested the hypothesis that Tau affects the BIN1–LVGCCβ1 interaction, using the BIN1–LVGCC-β1 PLA assay with and without pretreatment with Tau antisense oligonucleotide (ASO) ( Figure 5D ). We recently demonstrated that this ASO reduces Tau protein by about 50% under these conditions ( Rush et al, 2020 ). Tau reduction decreased BIN1–LVGCC-β1 interaction in primary hippocampal neurons, compared to neurons treated with a scrambled control ASO ( Figure 5E ), indicating that in cultured neurons the BIN1–LVGCC-β1 interaction is partially Tau-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…However, undesired effects such as memory deficits associated with the absence of Fyn (Grant et al, 1992) suggest that further investigations are required to achieve more desirable therapeutic results. The recent development of a cell-permeable peptide inhibitor of the Fyn-tau interaction yielded promising results, reducing the endogenous Fyn-tau interaction and tau phosphorylation (Rush et al, 2020). G9 monobodies have also been used, demonstrating efficiency in inhibiting Fyn-tau binding (Cochran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%